2020
DOI: 10.3390/su12218864
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison for Two Cable Extraction Machines in a Larix kaempferi (Lamb.) Carr. Plantation

Abstract: Forests in Korea are mainly located in steep mountainous areas, where small-shovel-based extraction technology is widely used, with the level of mechanization undoubtedly low due to financial limitations. On this steep terrain, a better approach may be to use cable yarders, which can offer high revenues through cable-based extraction. Therefore, improving the efficiency of cable yarding activities in good-quality timber forests is necessary. The main objectives of this study were to (1) evaluate the productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…These rates were significantly correlated with two different variables (Pearson's correlation, p < 0.05). This finding is consistent with those of previous studies such as Schweier et al [56], Baek et al [10], and Picchio et al [57], who reported that higher load capacities of yarders enable better performances, because they can control larger cycle log volumes compared to the machinery with low lifting capacities. This could be related to the low piece volume reported by Ghaffariyan [58] and Berendt et al [59], whose findings showed that increases in the harvesting productivity were associated with large log volumes, even though the extraction time per cycle increased.…”
Section: Effect Of Machinery On Productivitysupporting
confidence: 93%
“…These rates were significantly correlated with two different variables (Pearson's correlation, p < 0.05). This finding is consistent with those of previous studies such as Schweier et al [56], Baek et al [10], and Picchio et al [57], who reported that higher load capacities of yarders enable better performances, because they can control larger cycle log volumes compared to the machinery with low lifting capacities. This could be related to the low piece volume reported by Ghaffariyan [58] and Berendt et al [59], whose findings showed that increases in the harvesting productivity were associated with large log volumes, even though the extraction time per cycle increased.…”
Section: Effect Of Machinery On Productivitysupporting
confidence: 93%
“…The workload of the workers was also analyzed using VO 2max , increased heart rate (IHR), and relative heart rate (HRR). (21,25)…”
Section: Maximum Oxygen Consumptionmentioning
confidence: 99%
“…4). The resting heart rate (HR r , bpm), working heart rate (HR w , bpm), and maximum heart rate (HR max , bpm) were measured to analyze IHR (%) and HRR (%) as follows: (3,21) 100,…”
Section: Hrmentioning
confidence: 99%
See 1 more Smart Citation